If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4 = 11x + -10 Reorder the terms: -4 + 9x = 11x + -10 Reorder the terms: -4 + 9x = -10 + 11x Solving -4 + 9x = -10 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -4 + 9x + -11x = -10 + 11x + -11x Combine like terms: 9x + -11x = -2x -4 + -2x = -10 + 11x + -11x Combine like terms: 11x + -11x = 0 -4 + -2x = -10 + 0 -4 + -2x = -10 Add '4' to each side of the equation. -4 + 4 + -2x = -10 + 4 Combine like terms: -4 + 4 = 0 0 + -2x = -10 + 4 -2x = -10 + 4 Combine like terms: -10 + 4 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 5(a+3)=45 | | 27=-3(6) | | (1/3)(y+17)=3y-5(y-3) | | 9=7c-5 | | 12x-7=4x+14 | | 5.3x+1=3.8x-11 | | 2(3x-6.5)=20 | | (3x-8)+(2x+5)-(4x-8)= | | 5/13=x/8 | | 3x+1.4=x+1.8 | | 54/x=-6 | | 6-9x=-57 | | 4-3x=-8x+14 | | 5x=x+0.8 | | 35.4=-6g | | 2(z-4)+3z=4-(z+2) | | -7v+5v=-2-8 | | 11x=60.5 | | 4-3x=8x+14 | | 7y-10-5y+5=0 | | z-5z=-4 | | -(5x+2)=8 | | -2x+15=-17 | | 4u=-7 | | 44*.5= | | 3x^2-23x+13=0 | | -(11x^2+2x-1)= | | -6+5x=2+3x-2x | | 14v-16v=40 | | (1/5)x=-14 | | X/x+2=5/4 | | 77=4x+7x |